2016
DOI: 10.1080/10810730.2015.1103326
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Retweeting Behavior on Breast Cancer Social Networks: Network and Content Characteristics

Abstract: This study explored how social media, especially Twitter, serves as a viable place for communicating about cancer. Using a 2-step analytic method that combined social network analysis and computer-aided content analysis, this study investigated (a) how different types of network structures explain retweeting behavior and (b) which types of tweets are retweeted and why some messages generate more interaction among users. The analysis revealed that messages written by users who had a higher number of followers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 35 publications
1
61
1
Order By: Relevance
“…The size of follower networks has been shown to positively influence message passing (Kim, Hou, Han, & Himelboim, ; Suh et al., ). In general, larger networks predict increased message passing.…”
Section: Social Media and Risk Communicationmentioning
confidence: 99%
“…The size of follower networks has been shown to positively influence message passing (Kim, Hou, Han, & Himelboim, ; Suh et al., ). In general, larger networks predict increased message passing.…”
Section: Social Media and Risk Communicationmentioning
confidence: 99%
“…The attributes of the forwarding behavior consist of forwarding quantity, forwarding time, and forwarding intention according to the research purpose (Palovics, Daroczy, & Benczur, 2013). Researchers predict microblog forwarding behavior through a variety of algorithms and models, including the factor graph model (Yang, Guo, Cai, Tang, Li, Zhang, & Su, 2010), social network analysis and content analysis (Kim, Hou, Han, & Himelboim, 2016), the classification method (Hong, Dan, & Davison, 2011), the probabilistic collaborative filtering model (Zaman, Herbrich, Gael, & Stern, 2010), improved passive-aggressive algorithm (Petrovic, Osborne, & Lavrenko, 2011), the predictive model for retweeting based on conditional random fields (CRFs) (Peng, Zhu, Piao, & Yan, 2011), and so forth. It has been found that users' competition or cooperative interaction (Kong, Mao, & Liu, 2016), characteristics of the forwarding agent (Maleewong, 2016), and network structure (Gao, Ma, & Chen, 2014) all influence their forwarding behavior.…”
Section: Studies On Predicting Microblog Influencementioning
confidence: 99%
“…Online or internet interactions not based on a listserv or online support group can sometimes represent a less personal set of interactions, but they undoubtedly play a role in how people decide to approach decisions about cancer treatment. In a social network analysis study on Twitter and cancer messages, retweeting about breast cancer was predicted by in-degree centrality or the number of followers, betweenness centrality, and closeness centrality—especially the latter—but only around 7% of messages were retweeted ( 33 ). These scholars pose the interesting idea that the common conceptualization of opinion leaders as always followed by other consumers of information may need revision in order to capture the kinds of interactions involved in consuming and reproducing and revising information and in order to understand the diversity of roles in online dissemination that do not necessary fit a unidirectional flow or a hierarchical structure.…”
Section: Impersonal Relationsmentioning
confidence: 99%